Impact of left ventricular dysfunction on early and late outcomes in patients undergoing concomitant aortic valve replacement and coronary artery bypass graft surgery - Saxena, A.; Paramanathan, A.; Shi, W.; Dinh, D.; Reid, Christopher; Smith, J.; Shardey, G.; Newcomb, A. (2013)
Background: An increasing proportion of patients present for concomitant aortic valve replacement (AVR) and coronary artery bypass grafting (CABG) with left ventricular (LV) dysfunction. The aim of this study was to evaluate the early outcomes and late survival of patients with different degrees of LV function undergoing concomitant AVR and CABG. Methods: Between June 2001 and December 2009, patients undergoing concomitant AVR-CABG were identified from the Australian and New Zealand Society of Cardiac and Thoracic Surgeons Cardiac Surgery Database Program. Demographic, operative data and post-operative outcomes were compared between patients with normal (> 60%), moderately impaired (30-60%), and severely impaired (< 30%) estimated LV ejection fraction (LVEF). Independent risk factors for short-and long-term mortality were identified using binary logistic and Cox regression, respectively. Results: AVR-CABG was performed in 2,563 patients with a mean follow up of 36 months (range 0-106). 144 (5.6%) had severely impaired LVEF, 983 (38.3%) had moderately impaired LVEF while the remaining 1377 (53.7%) had normal LVEF. The 30-day mortality in patients with severely impaired, moderately impaired and normal LVEF was 9.0%, 4.3% and 2.9%, respectively. This was significant on univariate (p < 0.001) but not multivariate analysis (p = NS). Severely impaired, moderately impaired and normal LVEF patients experienced 5-year survivals of 63.7%, 77.1% and 82.5%, respectively. Severely impaired LVEF was an independent multivariable predictor of late mortality (HR 1.71; 95% CI 1.22-2.40; p = 0.002). Conclusions: Patients with severely impaired LVEF experience worse outcomes. However, in the era of modern surgery, this alone should not predicate exclusion, given the established benefits of surgery in this high-risk group. © 2013 Via Medica.